Ultra-high coercivity Sm-Co bulk magnets with remarkable thermal stability. (September 2022) - Park, Kwangjae; Hirayama, Yusuke; Wang, Jian; Kobashi, Makoto
Abstract: The Sm-Co bulk magnet prepared in this work using unique Sm-Co alloy nanopowder as a precursor prepared by the lox oxygen-induction thermal plasma (LO-ITP) process displays a giant coercivity of 4.1 MA/m (52 kOe) at 300 K, which is the highest coercivity among the reported rare-earth permanent bulk magnets with high density. The Sm-Co magnet has a high coercivity of 2.4 MA/m (30 kOe) at 473 K and 1.6 MA/m (20 kOe) at 573 K, which shows the good temperature coefficient of coercivity of −0.22%/K. The well-organized microstructure with fine Sm-Co alloy single-crystal grains with an average grain size of 0.63 μm, sharp grain boundary, and better crystallinity, leads to a huge coercivity and remarkable thermal stability. Graphical abstract: Image, graphical abstract